2022
DOI: 10.3390/v14050886
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Human Betaretrovirus from Patients with Primary Biliary Cholangitis

Abstract: A human betaretrovirus (HBRV) has been linked with the autoimmune liver disease, primary biliary cholangitis (PBC), and various cancers, including breast cancer and lymphoma. HBRV is closely related to the mouse mammary tumor virus, and represents the only exogenous betaretrovirus characterized in humans to date. Evidence of infection in patients with PBC has been demonstrated through the identification of proviral integration sites in lymphoid tissue, the major reservoir of infection, as well as biliary epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 93 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…The human betaretrovirus (HBRV) is the only exogenous betaretrovirus characterized in humans to date [68]. HBRV is not endogenously encoded in the human genome [68][69][70] but has been mistakenly been referred to as a human endogenous retrovirus by others [71].…”
Section: Betaretrovirusesmentioning
confidence: 99%
See 3 more Smart Citations
“…The human betaretrovirus (HBRV) is the only exogenous betaretrovirus characterized in humans to date [68]. HBRV is not endogenously encoded in the human genome [68][69][70] but has been mistakenly been referred to as a human endogenous retrovirus by others [71].…”
Section: Betaretrovirusesmentioning
confidence: 99%
“…The human betaretrovirus (HBRV) is the only exogenous betaretrovirus characterized in humans to date [68]. HBRV is not endogenously encoded in the human genome [68][69][70] but has been mistakenly been referred to as a human endogenous retrovirus by others [71]. HBRV shares very close nucleotide similarity with MMTV, to such an extent that human and mouse isolates are not easily distinguishable [54,68,70].…”
Section: Betaretrovirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…We have used MMTV as a model system to investigate retroviral intasome structure and function (14). MMTV has historically provided important insights into mechanisms of virally induced malignant transformation in mouse breast tissues (31) and has received recent attention due to its high degree of similarity to a betaretrovirus implicated in human autoimmune disease and cancer (32,33). Previously, we determined the structure of the MMTV CSC at ∼5-6 Å resolution (14), which revealed that flanking IN protomers can contribute to intasome assembly, but was insufficient to accurately describe structural interfaces, such as IN-vDNA contacts.…”
Section: Introductionmentioning
confidence: 99%